Muestreo intensivo del zooplancton en el sector inferior del Río Salado (Bs. As.) durante la ejecución de una obra hidráulica - Dippolito, Andrea (2009)
The objective of this study was to investigate changes occurred in the structure and dynamics of zooplankton community during dredging works made in the lower sector of Salado River (Buenos Aires, Argentina). The samples were taken before and during the extraction of a river restriction and the replacement of a bridge at one site upstream and other downstream of this hydraulic modification. The dredging works were made during low water period. Zooplankton samples were obtained filtering volumes of 10 l extracted at three points of a transect in the river channel (both banks and the middle of the course) during 14 weeks (weekly from March to June). Physical and chemical parameters were measured in situ with a multimeter. The conductivity decreased from 12,000 μS/cm (March-April) to 6,000 μS/cm (April-June). The zooplankton assemblages were correlated with factors such as conductivity, turbidity, water temperature, and phytoplankton density. Tintinids (Tintinnidium fluviatile and Codonella cratera) prevailed with high salinity whereas rotifers (Brachionus plicatilis and Keratella tropica, among others) dominated later. Microcrustaceans were scarce related to the conductivity of the river. The analyzed sites showed similar composition and abundance of zooplankton during all sampling period. We can assume that the effects of dredging works in low water conditions cause minimal downstream perturbations on zooplankton community.